The State Innovation Exchange and educational policy - Malin, Joel R.; Tan, Jing (Education Policy Analysis Archives, 2022)
Especially since 2010, conservative interests’ dominance at advancing their preferred policies across U.S. states has been clear, with large and escalating impacts in education. Although adversaries on the political left remain in catch-up mode, there have been auspicious developments. This study focuses on one of these, seeking to understand a uniquely positioned progressively state-focused policy organization called State Innovation Exchange (SiX). It was aimed to a) provide a valuable case study of perhaps the leading organization in this space, focusing on understanding its education policy footprint; b) further understandings of conflicts, tensions, and responses on the political left relative to education policy; and c) generate insights into contemporary sub-national policy mobility. We interviewed nine key stakeholders and analyzed electronic materials to address two research questions. Findings demonstrate SiX fulfills four main purposes: 1) building and sustaining cross-state progressive power; 2) acting as a counter; 3) fostering progressive leader development; and 4) advancing progressive policies/ideas. SiX shows an economics-focused agenda emphasizing working- and middle-class families, and education policy has not been a major, consistent area of emphasis. SiX does, however, play unique roles in education (as in other areas) by connecting state legislators and supporting their work. Specific to education, we surfaced some challenges SiX has faced in building alignment around a shared vision. We suggest, if SiX or a similarly situated organization can develop a clear education philosophy and policy agenda, it will be more effective at advancing its preferred policies, and in countering those being advanced by adversaries. Absent such shifts, we project continued conservative dominance of education policy at the state level.